Absenteísmo em contact center: estudo de caso com preditores micro e macroorganizacionais - Dias, Maiango (2005)
The general objective of this study was to investigate the capacity of explanation of Absenteeism among call center operators, through a set of micro and macro organizational variables, specifically, Perceived Organizational Support, Organizational Climate, Affective and Calculative Commitment and the Five Global Factors of Personality (Big Five) surveyed by the 16PF personality questionnaire. In order to investigate these relationships, a case study in a great contact center company was carried through, from a sample of 360 participants answered consistent and validated scales of perception about the measures under investigation (of Organizational Support, Organizational Climate, Affective and Calculative Commitment and the personality test). Four months after this procedure, the Absenteeism data (total of lost days) has been collected. Descriptive and correlate analyses and multiple regression stepwise have been, then, carried through, considering the measure of Absenteeism as a dependent variable. These procedures have been carried through for the complete sample and, later, for two groups of the same sample, of receptive and active call center operators. The results had indicated, essentially, that Absenteeism in the general sample (7,1%) and among receptive operators (6,8%) is slightly predicted by the model, including perception of Support (-) and the personality factor Self-control (+),a correlate of Conscientiousness (a personality factor of the Big Five model that has a recognized impact on the general performance). The model did not significantly explain variance in the active operators sample. The relationship between Perceived Organizational Support and Absenteeism is coherent with the model and international reports; otherwise, the relationship found between Self-control and the dependent variable is surprising, since it contests most of the literature. Amongst the results, the major predictive capacity of the macro-organizational variable over the only microorganizational variable that remained in the model must be pinpointed. This allows inferring that the environment has a greater control over the counter-productive behavior than the individual variable does. The results are discussed based on the literature, detaching the role of Perceived Organizational Support on the workers behavior. The conclusions of the study refute great part of the proposed model, but the limitations of the study are recognized and several perspectives for new research studies are offered. Contributions for the studied organization are also raised, as well as for practice among human resources professionals.